Three-Dimensional Movements and Habitat Selection of Young White Sharks (Carcharodon carcharias) Across a Temperate Continental Shelf Ecosystem - Shaw, Rachel L.; Curtis, Tobey H.; Metzger, Gregory; McCallister, Michael P.; Newton, Alisa; Fischer, G. Christopher; Ajemian, Matthew J. (Frontiers in Marine Science, 2021)
As highly mobile predators with extensive home ranges, some shark species often utilize a continuum of habitats across the continental shelf ranging from the surf zone to the open ocean. For many species, these cross-shelf distributions can change depending on ontogeny or seasonal conditions. Recent research has confirmed a white shark (Carcharodon carcharias) summer nursery off Long Island, New York; however, habitat characterization of this nursery has not yet been conducted nor has fine-scale analysis of vertical behavior. Between 2016 and 2019, 21 young-of-the-year and juvenile white sharks were fitted with satellite and acoustic tags to examine distribution and selection for a suite of oceanographic variables during their late summertime (i.e., August to October) residence in the New York Bight. Horizontal position estimates were used to extract a suite of environmental measurements via remote sensing platforms and were linked with vertical profiles to produce three-dimensional movements for a subset of individuals also fitted with pop-up satellite archival tags (n = 7). Sharks exhibited horizontal movements parallel to Long Island’s southern shoreline and coastal New Jersey, with distances from 0.1 to 131.5 km from shore. Log-likelihood chi-square analyses determined selection for waters with underlying bathymetry of 20–30 m, sea surface temperatures between 20.0 and 22.0°C, sea surface salinities between 31.0 and 32.0 ppt, and chlorophyll-a concentrations between 2.0 and 8.0 mg⋅m–3. Multiple individuals also traversed the mid- to outer shelf region after leaving the Montauk tagging area. Vertical depth profiles illustrated oscillations between the surface and 199 m of water, with an average swimming depth of 9.2 ± 8.9 m. Water column temperatures during these oscillations ranged between 7.9 and 26.2°C (mean = 19.5 ± 2.0°C) with several individuals traversing highly stratified regions presumably associated with a mid-shelf cold pool adjacent to the Hudson Shelf Valley. These results suggest young white sharks exhibit connectivity between the immediate shoreline and mid-continental shelf region, where they play important ecological roles as predators on a variety of species. Our study improves characterization of essential fish habitat for young white sharks and provides new insights into their reliance on this productive continental shelf ecosystem.